2012
DOI: 10.2478/v10152-012-0018-8
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological surveillance of gastrointestinal communicable diseases in Slovenia from 1999 to 2009

Abstract: Izvirni znanstveni članek UDK 616. 34-022(497.4) (Ur. l. RS, št. 33/2006, prečiščeno besedilo) Izvleček Uvod: Epidemiološko spremljanje črevesnih nalezljivih bolezni (ČNB) v Sloveniji temelji na zakonsko obvezni prijavi ČNB, ki jo določata Zakon o nalezljivih boleznih

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It has been reported that C. difficile [46] spores can survive temperatures and chemical treatment of typical hospital laundering cycles and that cross-contamination of C. difficile spores can occur on bed linen during a wash cycle. Therefore, the persistent nature of this organism must be considered by infection control personnel when implementing programs for laundering soiled and contaminated hospital linen (47). In our research, PCR yielded the lowest detectable survival of C. difficile spores on textiles after overnight drying in sample E with the lowest inoculated concentration before drying of (10 3 cfu/mL).…”
Section: Discussionmentioning
confidence: 63%
“…It has been reported that C. difficile [46] spores can survive temperatures and chemical treatment of typical hospital laundering cycles and that cross-contamination of C. difficile spores can occur on bed linen during a wash cycle. Therefore, the persistent nature of this organism must be considered by infection control personnel when implementing programs for laundering soiled and contaminated hospital linen (47). In our research, PCR yielded the lowest detectable survival of C. difficile spores on textiles after overnight drying in sample E with the lowest inoculated concentration before drying of (10 3 cfu/mL).…”
Section: Discussionmentioning
confidence: 63%
“…The recommendations of the Brazilian Public Health Guideline for Tuberculosis Prevention, reviewed in 2020, did not include patients receiving immunosuppressive therapy in the risk group for screening of latent TB[ 6 ]. However, consensus from endemic countries suggests investigation and treatment of latent TB before starting immunosuppressive therapy[ 7 - 9 ].…”
Section: To the Editormentioning
confidence: 99%
“…In Slovenia, notifications of infectious diarrhoea comprise a quarter of all infectious diseases notifications, remaining an important public health issue ( 13 ). Food-borne illness and outbreaks caused by C. perfringens are reportable.…”
Section: Introductionmentioning
confidence: 99%